Early renal arterial rupture and arterial pseudoaneurysm in graft kidneys from the same deceased donor - Lin, Yu-Hua (Tzu Chi Med J, 2018)
Vascular complications are serious problems after kidney transplantation. An aneurysm or rupture in a graft artery is a rare but potentially devastating complication, which may lead to renal function impairment, graft loss, or even death. In this paper, we present two rare vascular complications in the early postoperative course after renal transplantation from the same deceased donor. In the first case, a 49-year-old woman who had spontaneous graft arterial rupture 13 days after kidney transplantation presented with sudden distension in the right lower abdomen. In the second case, a 56-year-old woman recipient with a graft renal arterial pseudoaneurysm presented with decreased urine output and deteriorating renal function 32 days after transplantation. Immediate surgical repair was performed, and fibrin sealant was applied to strengthen the fragile renal arterial wall. Although the function of both graft kidneys recovered well after surgery, the first graft kidney was removed 2 months later because of repeated fungal and bacterial infections. Aggressive surgical reconstruction may preserve graft kidneys in patients with vascular complications after kidney transplantation, but recovery of the graft condition remains a demanding challenge in renal transplantation.